If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42+9y+4=-10
We move all terms to the left:
42+9y+4-(-10)=0
We add all the numbers together, and all the variables
9y+56=0
We move all terms containing y to the left, all other terms to the right
9y=-56
y=-56/9
y=-6+2/9
| 103+42+x=180 | | d/2+9=10 | | 4x-2-7x=119 | | 11=18+8f | | 65+x+x=128 | | 10(b+2)=20 | | 109+42+x=180 | | q/9+5=10 | | 10x+5-2x=3x+25 | | 4=t/2.5 | | 4u+19=-1 | | 6-5y=3y-2 | | 8(-2x-4)+13=52 | | t/19+9=14 | | -(x-5)-2x=4 | | 8x+3x-243=76 | | c+14/3=14 | | 5(2q-8)=10 | | 4-7(1-8c)=-20 | | 4x+2=8-10 | | x+59+121=180 | | 6x-109-11x=66 | | 10x+85=180 | | 2(d+7)=20 | | -2(3x-8)=2x-8 | | 135+2n=11+2n | | X+3/3=2x-4/5 | | c/11+9=12 | | 7(3x-2)-6=-3(7x+5)-5 | | s+1/2=19 | | 8x-2=(x-1)+16 | | 2-8u=6 |